Analysis of in-hospital mortality and associated risk factors in hospitalized elderly patients with an Omicron infection - Liu, Yan; Liu, Jiao; Wang, Ya-Nan; Zhao, Yu-Tong; Zhang, Jie; Cao, Jing (The Journal of Infection in Developing Countries, 2026)
Introduction: The aim of this study was to evaluate the in-hospital mortality rate and associated risk factors in elderly patients hospitalized with an Omicron coronavirus disease 2019 (COVID-19) infection. Methodology: This retrospective cohort study included 137 elderly patients with Omicron infection. The cases were divided into survival and mortality groups based on the discharge outcomes. The basic data were collected. A logistic regression model was used to analyze the risk factors for mortality. Results: The in-hospital mortality rate was 25.54% (102 survivors, 35 non-survivors). The mean age was higher in the mortality group. Shock and dyspnea were more common in the mortality group (p = 0.041). Multivariable logistic regression analysis concluded that advanced age (odds ratio, (OR) = 2.158, 95% confidence interval (CI): 1.183–3.368), shock (OR = 2.876, 95% CI: 1.538–8.304), high neutrophil-to-lymphocyte ratio (NLR; OR = 1.872, 95% CI: 1.060–2.424), radiographic pleural effusion (OR = 1.756, 95% CI: 1.592–3.662), and elevated fasting glucose (OR = 1.785, 95% CI: 1.263–3.821) were independent predictors of in-hospital mortality. The Hosmer–Lemeshow test showed that the proposed model had a good fit with observed values (χ2 = 4.681, p = 0.341). The receiver operating characteristic curve indicated that the proposed model had an area under the curve of 0.791 for predicting mortality, with a sensitivity of 83.9% and specificity of 61.5%. Conclusions: The in-hospital mortality rates were high in elderly patients with Omicron infection. Advanced age, glucose level, shock, NLR, and pleural effusion were identified as risk factors.